Enhanced diaphragm excursion and exercise tolerance in COPD patients through inspiratory muscle training after standardised pulmonary rehabilitation: randomised controlled trial - Masashi Shiraishi; Yuji Higashimoto; Ryuji Sugiya; Hiroki Mizusawa; Yu Takeda; Masaya Noguchi; Osamu Nishiyama; Ryo Yamazaki; Shintarou Kudo; Tamotsu Kimura; Hisako Matsumoto (ERJ Open Research)
Objective Inspiratory muscle training (IMT) is used to improve inspiratory muscle strength in patients with COPD. However, the effect of IMT on diaphragmatic function has not yet been thoroughly evaluated. This study aimed to evaluate the effect of IMT on maximum diaphragmatic excursion (DEmax) using ultrasonography in patients with COPD. Methods This was a single-centre, randomised, prospective, parallel-group, unblinded controlled trial involving 38 participants with stable COPD. Participants underwent a standardised 12-week pulmonary rehabilitation (PR) programme followed by a 12-week IMT programme, consisting of home-based IMT and low-frequency outpatient PR sessions supervised by physiotherapists (once every 2 weeks), versus low-frequency outpatient PR alone as a control. The DEmax and exercise tolerance were measured. Results Out of the 38 patients initially enrolled in the PR programme, 33 successfully completed it and were subsequently randomised to the IMT programme. Finally, 15 (94%) and 14 (88%) patients from the IMT and control groups, respectively, completed the study. Following the IMT programme, DEmax increased in the IMT group (mean±sd 50.1±7.6 mm to 60.6±8.0 mm, p<0.001), but not in the control group (47.4±7.9 mm to 46.9±8.3 mm, p=0.10). Changes in DEmax and exercise tolerance (peak oxygen uptake) were greater in the IMT group than in the control group (both p<0.01). Conclusions IMT following the PR programme improved DEmax and exercise tolerance. Therefore, DEmax may be an important outcome of IMT.